Debilitative interpretations of competitive anxiety: A qualitative examination of elite performers - Hanton, S.; Wadey, R.; Connaughton, D. (European Journal of Sport Science, 2005)
Research has not accounted for a small but significant proportion of elite performers who consistently report debilitative interpretations of competitive anxiety-related symptoms. Interviews were used to investigate elite athletes` precompetitive thoughts, feelings, and mental strategies underlying symptom interpretation. Six male athletes, from a variety of sports (M age?=?23.3, SD=2.2), who were currently competing within the UK, were found to hold debilitative interpretations. Data were drawn from verbatim transcripts and the content analysed. Four general dimensions traced the participants` precompetitive states and mental skills from early competitive experiences to the present day. Findings indicated that the participants reported early debilitating symptoms, which became habituated throughout their respective careers. Possible explanations as to why these elite performers consistently reported negative interpretations related to mental preparation and effectiveness, psychological skills, coping strategies, perceptions of control, and perceived self-confidence levels. The way in which the athletes are able to compete at an elite level, despite reporting debilitative interpretations, is also discussed.